Whole-exome sequencing reanalysis at 12 months boosts diagnosis and is cost-effective when applied early in Mendelian disorders. (December 2018) - Ewans, Lisa; Schofield, Deborah; Shrestha, Rupendra; Zhu, Ying; Gayevskiy, Velimir; Ying, Kevin; Walsh, Corrina; Lee, Eric; Kirk, Edwin; Colley, Alison; Ellaway, Carolyn; Turner, Anne; et al.
Abstract Purpose Whole-exome sequencing (WES) has revolutionized Mendelian diagnostics, however, there is no consensus on the timing of data review in undiagnosed individuals and only preliminary data on the cost-effectiveness of this technology. We aimed to assess the utility of WES data reanalysis for diagnosis in Mendelian disorders and to analyze the cost-effectiveness of this technology compared with a traditional diagnostic pathway. Methods WES was applied to a cohort of 54 patients from 37 families with a variety of Mendelian disorders to identify the genetic etiology. Reanalysis was performed after 12 months with an improved WES diagnostic pipeline. A comparison was made between costs of a modeled WES pathway and a traditional diagnostic pathway in a cohort with intellectual disability (ID). Results Reanalysis of WES data at 12 months improved diagnostic success from 30 to 41% due to interim publication of disease genes, expanded phenotype data from referrer, and an improved bioinformatics pipeline. Cost analysis on the ID cohort showed average cost savings of US$586 (AU$782) for each additional diagnosis. Conclusion Early application of WES in Mendelian disorders is cost-effective and reanalysis of an undiagnosed individual at a 12-month time point increases total diagnoses by 11%.